CROWDFUNDING: AS AN ALTERNATIVE TO ISLAMIC FUNDING - Rizka Estisia Pratiwi; Nadia Meirani; Khumairah Khumairah; Mohd. Shafiz Saharan; Hasrol Effendy Hassan (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
This study aimed to explore deeper conceptually about crowdfunding as alternative funding according to Islamic principles. There are still limitations to looking for similar research, so this research will be fundamental to study, especially for business actors or investors who want to take part in a halal business and have a high social value. Based on published studies and indexed by Scopus, this research is based on bibliometric research to see the conceptual development of Islamic crowdfunding. The bibliometric approach to reviews has gained popularity due to several factors, including the introduction of software, cross-disciplinary methods, and increased ability to handle large volumes of data. The results showed that the development of literature on Islam Crowdfunding as alternative Islamic funding had made rapid progress in recent years. The existence of public awareness of social values and welfare is one of the factors that support the success of Islamic crowdfunding. Crowdfunding is beneficial for funding companies. It dramatically facilitates investors in getting access to information related to the distribution of funds that must be done as well as from the side of the return of funds.